Low feature dimension in image steganographic recognition - Ismail Taha Ahmed; Norziana Jamil; Baraa Tareq Hammad (Institute of Advanced Engineering and Science, 2022)
Steganalysis aids in the detection of steganographic data without the need to know the embedding algorithm or the